First record of click Beetle Agriotes lineatus (Linneaus ) (Coleoptera : Elateridae )In the middle of Iraq (Baghdad Science Journal, 2011)
Trials were carried out in the middle of Iraq ( 3 different sites ) during 2009 to detecation and determined the seasonal occurrence of Agriotes lineatus L. Three YATOR funnel traps were used in each of these sites which baited with the specific pheromone of A. lineatus from the first of March to the end of October in the College of Agriculture - Abu- Ghraib / Provenance of Baghdad and AL-Nile / Provenance of Babylon , while in AL-Radhwania was used through May- June. Pheromone dispenser were changed every 6 weeks in each of these traps . Males of A. lineatus were found in all of the three sites , and the total number capture were 208 , 897 and 57 male / 3 traps / season in College of Agriculture , AL-Nile and AL-Radhwania respectively . This is the first record of this species in Iraq . Seasonal occurrence was lasted from mid of April to mid of July with peak population in the end of May in college of Agriculture, while lasted from April to first of July with peak population at the first of June in AL-Nile site. The high population density of Males in AL-Nile site indicate the economic important of A. lineatus in this site on many crops epically on Potato crop .